PWE-049 Vaccination of inflammatory bowel disease patients on immunomodulators and biologics. (22nd June 2015) - Tan, J; Yap, K; Hong, L; Babu, P
Abstract : Introduction: Immunomodulators (IM) and Biologics are increasingly used to treat Inflammatory Bowel Disease early during the disease course. The risk of opportunistic infections associated with their use is high. Guidelines from the BSG and ECCO advice to screen and vaccinate patients when IM or Biologics are considered for treatment. Vaccinations recommended include Varicella Zoster (VZ) and Hepatitis B (HBV) in seronegative patients, annual Influenza, Pneumococcal vaccine every 3 yrs and Human Papilloma Virus (HPV) for girls. Although Consultants are aware of these guidance, the implementation was felt to be poor in our unit. Method: The aim of this audit was to study the number of patients on IM and Biologics who have been screened and vaccinated for opportunistic infections. Patients were identified at random from the IBD database and demographic details collected. Patients and their GPs were interviewed to obtain vaccination history and exposure to chicken pox. The microbiology records were interrogated to obtain results of VZV and HBV serology. Results: Data was collected for 102 patients (30 UC and 72 Crohns). There were 52 females. The median age was 46 yrs (Range: 20–89 yrs) and 40 patients (39%)were over 50 yrs old. 75 patients were on AZA/6MP, 3 on Methotrexate and 25 on Biologics. 40% of patients had been on IM for over 3 yrs. Hepatitis serology was checked in 49 (48%) patients but none of the seronegative were vaccinated. Varicella (VZV) serology was checked in 22 patients and 24 had a history of chicken pox but none of the seronegative were vaccinated although one patient refused. No females received HPV vaccine. Only 64 (63%) patients had yearly influenza vaccine and 1 had an allergy. Less than 25% had received the pneumococcal vaccine. Conclusion: Our audit confirms poor compliance with the vaccination recommendations for the IBD patients at high risk. Awareness of this guidance although present among Consultants has not been implemented. Knowledge of this guidance is poor among specialist Nurses. This audit has informed the need for education of both primary and secondary care and introduction of a checklist for all monitoring including this information in all IBD communication as an aide memoire. We aim to repeat the audit in 4 months and hope to see an improvement. Disclosure of interest: None Declared.